Higher literacy is associated with better white matter integrity and cognition in middle age. Issue 1 (9th December 2022) - de Resende, Elisa de Paula França; Xia, Feng; Sidney, Stephen; Launer, Lenore J.; Schreiner, Pamela J.; Erus, Guray; Bryan, Nick; Yaffe, Kristine
Abstract: Introduction: Literacy can be a better measure of quality of education. Its association with brain health in midlife has not been thoroughly investigated. Methods: We studied, cross‐sectionally, 616 middle‐aged adults (mean age of 55.1 ± 3.6 years, 53% female and 38% Black) from the Coronary Artery Risk Development in Young Adults (CARDIA) study. We correlated literacy with cognitive tests, gray matter volumes, and fractional anisotropy (FA) values (indirect measures of white matter integrity) using linear regression. Results: The higher‐literacy group ( n = 499) performed better than the low‐literacy group ( n = 117) on all cognitive tests. There was no association between literacy and gray matter volumes. The higher‐literacy group had greater total‐brain FA and higher temporal, parietal, and occipital FA values after multivariable adjustments. Discussion: Higher literacy is associated with higher white matter integrity as well as with better cognitive performance in middle‐aged adults. These results highlight the importance of focusing on midlife interventions to improve literacy skills.